Genome-Wide Analysis of Genes Encoding Methionine-Rich Proteins in Arabidopsis and Soybean Suggesting Their Roles in the Adaptation of Plants to Abiotic Stress - Ha Duc Chu; Quynh Ngoc Le; Huy Quang Nguyen; Dung Tien Le (International Journal of Genomics)
Oxidation and reduction of methionine (Met) play important roles in scavenging reactive oxygen species (ROS) and signaling in living organisms. To understand the impacts of Met oxidation and reduction in plants during stress, we surveyed the genomes of Arabidopsis and soybean (Glycine max L.) for genes encoding Met-rich proteins (MRPs). We found 121 and 213 genes encoding MRPs in Arabidopsis and soybean, respectively. Gene annotation indicated that those with known function are involved in vital cellular processes such as transcriptional control, calcium signaling, protein modification, and metal transport. Next, we analyzed the transcript levels of MRP-coding genes under normal and stress conditions. We found that 57 AtMRPs were responsive either to drought or to high salinity stress in Arabidopsis; 35 GmMRPs were responsive to drought in the leaf of late vegetative or early reproductive stages of soybean. Among the MRP genes with a known function, the majority of the abiotic stress-responsive genes are involved in transcription control and calcium signaling. Finally, Arabidopsis plant which overexpressed an MRP-coding gene, whose transcripts were downregulated by abiotic stress, was more sensitive to paraquat than the control. Taken together, our report indicates that MRPs participate in various vital processes of plants under normal and stress conditions.